Stercoral Ulcer Presenting in a Patient with Cauda Equina Syndrome Secondary to Postoperative Epidural Hematoma - Min-Seok Kang; In-Seok Son; Suk-Ha Lee; Tae-Hoon Kim (Medicina, 2023)
Chronic constipation can lead to fecal impaction in the large bowel, which can cause pressure necrosis followed by perforation, known as a stercoral ulcer. In extensive posterior thoracolumbar surgery, a long operation time, large blood loss, and perioperative narcotic use may aggravate constipation. Moreover, sacral root palsy due to cauda equina syndrome (CES) can lead to the deterioration of fecal impaction. This report describes the case of a 77-year-old woman with CES who presented with saddle anesthesia, neurogenic bladder, bowel incontinence, and paraplegia. Five days prior, she had undergone extended posterior lumbar interbody fusion from L1 to L5. Lumbar magnetic resonance imaging (MRI) showed an extended epidural hematoma. After urgent neural decompression, she gradually recovered from the saddle anesthesia, leg pain, and paraplegia over 3 weeks. Thereafter, the patient suddenly developed massive hematochezia and hemorrhagic shock. Urgent colonoscopy was performed, and a stercoral ulcer in the sigmoid colon was diagnosed. After 4 weeks of intensive care for hemorrhagic shock, pneumonia, and systemic sepsis, the patient was transferred to a general ward for intensive rehabilitation. One year after the operation, she was able to walk with assistance, and her urinary and bowel incontinence completely recovered. Chronic constipation, a common clinical problem, can sometimes cause relatively obscure but potentially life-threatening complications such as stercoral ulceration. Possible factors including advanced age, extensive spinal surgeries, prolonged operation time, significant blood loss, perioperative narcotic use, and the presence of spinal cord injury might contribute to the development of this condition. It highlights the importance of recognizing the potential development of stercoral ulcers in patients with CES and emphasizes the need for prompt diagnosis and management to avert catastrophic complications.